2022
DOI: 10.1001/jamaoncol.2022.2952
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Lung Cancer Risk Among Smokers for Whom Annual Screening Is Not Recommended

Abstract: ImportanceThe US Preventive Services Task Force does not recommend annual lung cancer screening with low-dose computed tomography (LDCT) for adults aged 50 to 80 years who are former smokers with 20 or more pack-years of smoking who quit 15 or more years ago or current smokers with less than 20 pack-years of smoking.ObjectiveTo determine the risk of lung cancer in older smokers for whom LDCT screening is not recommended.Design, Settings, and ParticipantsThis cohort study used the Cardiovascular Health Study (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Six fair‐quality studies provide moderate‐certainty evidence that the relative risk (RR) or odds of lung cancer remains elevated beyond 15 YSQ (see Tables 3 and ) 13,14,19,20,33,34 . Three prospective cohort studies (i.e., the CPS‐II nutrition cohort, n = 184,194 33 ; the Cardiovascular Health Study, n = 4279 19 ; and the Framingham Heart Study, n = 8907), 13,19,33 one case–control study (BLCS, n = 5503), 34 and one cross‐sectional analysis (PLCO, n = 108,526), 14 were conducted in the United States. The remaining study was the Singapore Chinese Health Study ( n = 48,251), 20 which examined a cohort of Chinese residents living in Singapore 20 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six fair‐quality studies provide moderate‐certainty evidence that the relative risk (RR) or odds of lung cancer remains elevated beyond 15 YSQ (see Tables 3 and ) 13,14,19,20,33,34 . Three prospective cohort studies (i.e., the CPS‐II nutrition cohort, n = 184,194 33 ; the Cardiovascular Health Study, n = 4279 19 ; and the Framingham Heart Study, n = 8907), 13,19,33 one case–control study (BLCS, n = 5503), 34 and one cross‐sectional analysis (PLCO, n = 108,526), 14 were conducted in the United States. The remaining study was the Singapore Chinese Health Study ( n = 48,251), 20 which examined a cohort of Chinese residents living in Singapore 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Three fair-quality studies contribute to low-certainty evidence that lung cancer incidence remains elevated beyond 15 YSQ (see Tables 3 and S4). 14,19,20 A prospective cohort study (the Cardiovascular Health Study, n = 4279) reported cumulative incidences of 5.0% and 10.1% versus 0.5% when comparing those who had ≥15 YSQ versus <15 YSQ, respectively, with individuals who never smoked (Tables 2 and 4). 19 Two articles reported lung cancer incidence rates beyond 15 YSQ.…”
Section: Lung Cancer Incidence By Years Since Quitmentioning
confidence: 99%
See 1 more Smart Citation
“…The US Preventive Services Task Force(USPSTF) recommends annual lung cancer screening with LDCT for adults aged 50 to 80 years with a history of ≥20 pack‐years of smoking and currently smoke or had quit within the past 15 years 28 . In a recent study, compared with non‐smokers, though the lung cancer incidence of heavy smokers (≥20 pack‐year smoking history and ≥15 years since quitting) increased significantly, the incidence in non‐heavy smokers (<20 pack‐year smoking history among former smokers and ≥15 years since quitting or <15 years since quitting and current smoker) also significantly increased from 3.09 to 9.35 29 . Although studies in Henan, China showed that smokers with a smoking history of ≥30 pack‐years was a risk factor for lung cancer, 30 the above study indicated that smokers not recommended to undergo LDCT screening need to be identified as high‐risk subsets for screening as well.…”
Section: Discussionmentioning
confidence: 96%
“…Further, the majority of lung cancers are diagnosed in individuals that do not meet screening eligibility criteria ( 4 ). Despite the expanded screening eligibility with the revised United States Preventive Services Task Force (USPSTF) guidelines ( 5 ), individuals that do not meet screening criteria have a high risk of lung cancer ( 6 ), supporting the need for prediction tools that can facilitate the identification of high-risk individuals and the adoption of screening in clinical practice.…”
Section: Introductionmentioning
confidence: 99%